STRATEGI PENGEMBANGAN KAWASAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN MERAUKE - Sultan; Mujiati; Rante , Harmonis (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2025)
Merauke Regency has vast and strategic agricultural land potential as a national food basket, but ecological, social, and infrastructure challenges remain obstacles to the development of sustainable farm areas. This study aimsto formulate a strategy for developing a sustainable food-based agricultural area that is adaptive to local conditionsin Merauke. The method used is a qualitative-descriptive approach through literature review and analysis of strategiesbased on regional potential. The study findings indicate that strategies encompassing optimal land use, technologyapplication, wise natural resource management, infrastructure strengthening, community empowerment, and greeneconomy-based policies can drive the transformation of Merauke's agriculture into a productive, efficient, andsustainable system. Implementation recommendations include a multi-stakeholder collaborative approach,regulatory support, and risk mapping based on spatial data.